The impact of a performance profiling intervention on athletes' intrinsic motivation - Weston, N. J.V.; Greenlees, I. A.; Thelwell, R. C. (Research Quarterly for Exercise and Sport, 2011)
Originally developed by Butler (1989) with the Great Britain Olympic boxing team, performance profiling is an assessment tool primarily used by sport psychologists to enhance athlete awareness (Butier, 1989, 1997; Butler & Hardy, 1992; Butler, Smith, & Irwin, 1993). Through an understanding of selected principles of personal construct theory (Kelly, 1955), Butler and Hardy (1992) developed a client-centered performance assessment technique that asks athletes (either individually or as part of a group) to identify the qualities essential to their performance and then rate themselves on those qualities. The completed profile provides the athlete, the coach, and psychologist with a visual representation of the athlete's perception of his or her performance and hence can be used as a basis to set goals and structure future training interventions (Butler et al., 1993).